(untitled) (Bangladesh Journal of Neurosurgery, 2022)
Mucormycosis is a fungus found in the environment. In an immunocompetent person, it may cause localized infection. Invasive Mucormycosis has a poor prognosis. We describe a case of cerebral mucormycosis in an immune competent patient. A 46-yearold man was admitted with seizures and headaches. Magnetic resonance imaging (MRI) of the brain showed contrast enhancing lesion at the right frontal region. Excision biopsies showed granulomatous reactions, compatible with mucormycosis. Amphotericin B was begun. The results of testing for human immunodeficiency virus (HIV) were negative. Unfortunately the patient died on twenty-fifth postoperative day. Most cases of invasive mucormycosis show that this organism is pathogenic in immuno-compromised patients; however, some case reports show that invasive mucormycosis may not be so rare in immunocompetent patients. In these patients, virulent and drug-resistant forms of mucormycosis may be responsible for the disease, and treatment with antifungal agents are often ineffective, so that surgical excision is required. Bang. J Neurosurgery 2022; 11(2): 141-144